2023
DOI: 10.1093/ajh/hpad055
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Allisartan Isoproxil in the Treatment of Mild-to-Moderate Essential Hypertension

Abstract: BACKGROUND Allisartan isoproxil is a selective nonpeptide angiotensin II (AT1) receptor blocker developed by China, this study aimed to assess its clinical efficacy for essential hypertension (EH). METHODS Patients with mild-to-moderate EH, selected at 44 sites in China from September 9, 2016, to December 7, 2018, were administered 240 mg allisartan isoproxil daily for 4 weeks. Patients with controlled blood pressure (BP) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…These results indicate that, in addition to blocking the activity of renin-angiotensin-aldosterone system (RAAS), allisartan may also exert these effects via other auxiliary mechanisms. Clinical studies have demonstrated that allisartan could effectively reduce the serum uric acid (UA) level in hypertensive patients with hyperuricemia [ 94 , 95 ]. Animal studies in zebrafish hyperuricemia model have shown that allisartan could significantly upregulate intestinal urate transporters such as ABCG2, PDZK1, and SLC2A9, which might be the possible mechanism of UA reduction [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that, in addition to blocking the activity of renin-angiotensin-aldosterone system (RAAS), allisartan may also exert these effects via other auxiliary mechanisms. Clinical studies have demonstrated that allisartan could effectively reduce the serum uric acid (UA) level in hypertensive patients with hyperuricemia [ 94 , 95 ]. Animal studies in zebrafish hyperuricemia model have shown that allisartan could significantly upregulate intestinal urate transporters such as ABCG2, PDZK1, and SLC2A9, which might be the possible mechanism of UA reduction [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guidelines for hypertension management commonly recommend combination therapy involving a renin-angiotensin system inhibitor with a calcium channel blocker or combined diuretic ( 43 ). A multicenter, prospective, open phase IV clinical trial conducted by Wang et al ( 27 ) investigated the antihypertensive efficacy of Allisartan Isoproxil combined with indapamide or amlodipine in patients who did not meet monotherapy standards. From baseline to 12 weeks, SBP decreased by 19.1 ± 11.7 mmHg and DBP decreased by 10.8 ± 8.7 mmHg.…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have demonstrated its ability to lower blood pressure, mitigate inflammation and oxidative stress, and improve cardiac remodeling and cardiac dysfunction with minimal toxicity ( 26 ). Several clinical studies have demonstrated the favorable antihypertensive impact of Allisartan Isoproxil on mild to moderate essential hypertension, highlighting its safety and effectiveness in blood pressure reduction and organ protection ( 27 , 28 ). Nonetheless, despite these promising outcomes, the existing evidence base remains inadequately substantiated.…”
Section: Introductionmentioning
confidence: 99%
“…According to a study of 24‐h ABPM, after oral administration of 240 mg allisartan isoproxil once a day in the morning for 12 weeks, daytime and nighttime ambulatory BP decreased by 9.9/5.4 and 10.4/5.4 mm Hg, respectively. 77 In addition to blocking the renin‐angiotensin‐aldosterone system (RAAS), the dominant effect of allisartan isoproxil on reducing nighttime BP may be related to its effects on reduction of uric acid and sodium reabsorption. 78 …”
Section: Treatmentmentioning
confidence: 99%